Reputation: 2229
Is there a way to convert the property selector Expression<Func<T, TProperty>>
to Expression<Func<object, object>>
and vice versa? I already know how to convert to Expression<Func<T, object>>
using...
Expression<Func<T, TProperty>> oldExp;
Expression.Lambda<Func<T, object>>(Expression.Convert(oldExp.Body, typeof(object)), oldExp.Parameters);
... but I need to effectively cast both, the argument and the result of the function, not just e.g replace them with a ExpressionVisitor
because they need to be casted back later.
Upvotes: 5
Views: 1340
Reputation: 3337
You were correct that you need to use an ExpressionVisitor and ExpressionConvert.
Here are the two methods that you asked for (as well as some support methods):
public Expression<Func<object, object>> ConvertToObject<TParm, TReturn>(Expression<Func<TParm, TReturn>> input)
{
var parm = Expression.Parameter(typeof(object));
var castParm = Expression.Convert(parm, typeof(TParm));
var body = ReplaceExpression(input.Body, input.Parameters[0], castParm);
body = Expression.Convert(body, typeof(object));
return Expression.Lambda<Func<object, object>>(body, parm);
}
public Expression<Func<TParm, TReturn>> ConvertBack<TParm, TReturn>(Expression<Func<object, object>> input)
{
var parm = Expression.Parameter(typeof(TParm));
var castParm = Expression.Convert(parm, typeof(object));
var body = ReplaceExpression(input.Body, input.Parameters[0], castParm);
body = Expression.Convert(body, typeof(TReturn));
return Expression.Lambda<Func<TParm, TReturn>>(body, parm);
}
Expression ReplaceExpression(Expression body, Expression source, Expression dest)
{
var replacer = new ExpressionReplacer(source, dest);
return replacer.Visit(body);
}
public class ExpressionReplacer : ExpressionVisitor
{
Expression _source;
Expression _dest;
public ExpressionReplacer(Expression source, Expression dest)
{
_source = source;
_dest = dest;
}
public override Expression Visit(Expression node)
{
if (node == _source)
return _dest;
return base.Visit(node);
}
}
Sample usage:
Expression<Func<Customer, string>> expression = c => c.Name;
var convertedExpression = ConvertToObject<Customer, string>(expression);
var backExpression = ConvertBack<Customer, string>(convertedExpression);
Of course we can replace the original two methods with one method with more type parameters:
public Expression<Func<TTargetParm, TTargetReturn>> ConvertGeneric<TParm, TReturn, TTargetParm, TTargetReturn>(Expression<Func<TParm, TReturn>> input)
{
var parm = Expression.Parameter(typeof(TTargetParm));
var castParm = Expression.Convert(parm, typeof(TParm));
var body = ReplaceExpression(input.Body, input.Parameters[0], castParm);
body = Expression.Convert(body, typeof(TTargetReturn));
return Expression.Lambda<Func<TTargetParm, TTargetReturn>>(body, parm);
}
Sample usage:
Expression<Func<Customer, string>> expression = c => c.Name;
var convertedExpression = ConvertGeneric<Customer, string, object, object>(expression);
var backExpression = ConvertGeneric<object, object, Customer, string>(convertedExpression);
Upvotes: 8